2014
DOI: 10.1021/es404951y
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium Immobilization and Remobilization by Soil Mineral and Organic Matter in the Far-Field of the Savannah River Site, U.S.

Abstract: To study the effects of natural organic matter (NOM) on Pu sorption, Pu(IV) and (V) were amended at environmentally relevant concentrations (10(-14) M) to two soils of contrasting particulate NOM concentrations collected from the F-Area of the Savannah River Site. More Pu(IV) than (V) was bound to soil colloidal organic matter (COM). A de-ashed humic acid (i.e., metals being removed) scavenged more Pu(IV,V) into its colloidal fraction than the original HA incorporated into its colloidal fraction, and an invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 56 publications
2
47
0
Order By: Relevance
“…4 The majority of the mobile colloidal Pu was contained in a subfraction that was separated via an isoelectric focusing (IEF) electrophoresis experiment and found to concentrate around the IEF range of 4.1−5.6 (defined as "SRS IEF colloid"). 7 Elevated pH values, as a result of the basin closure and remediation strategies, led to Pu remobilization by complexation with colloidal organic matter and subsequent desorption from soil particles in the downstream wetland sediment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4 The majority of the mobile colloidal Pu was contained in a subfraction that was separated via an isoelectric focusing (IEF) electrophoresis experiment and found to concentrate around the IEF range of 4.1−5.6 (defined as "SRS IEF colloid"). 7 Elevated pH values, as a result of the basin closure and remediation strategies, led to Pu remobilization by complexation with colloidal organic matter and subsequent desorption from soil particles in the downstream wetland sediment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Blinova et al 51 argued that Pu−FA complexation will result in more mobile Pu(IV) species at higher pH values (i.e., pH 6), where one would expect lower FA sorption and larger FA fractions remaining in solution. Last, Xu et al 33 determined that, at increasing pH values, larger fractions of Pu became associated with organic-rich colloids compared to the particulate phase of an environmental soil sample.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…31 Second, NOM in solution may control Pu redox chemistry 35 and therefore indirectly affect Pu sorption characteristics (e.g., the relative abundance of Pu(IV) versus Pu(V) in solution will influence Pu sorption affinities). In addition to dissolved NOM, organic-rich colloids can alter Pu partitioning between dissolved, colloidal, and particulate phases and enhance Pu mobility, as has been demonstrated under both laboratory 33 and field conditions. 28,36 Besides dissolved and colloidal organic matter, we believe that the specific role of organic matter coatings, commonly found on mineral surfaces in the environment, 37,38 needs to be taken into account for the evaluation of organic matter effects on Pu mobility.…”
Section: ■ Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Despite the low Kd values of Pu in soils and sediments (McCubbin et al, 2004;Serne, 2007), the potential remobilization of small quantities of the actinide is still a concern (Kersting et al, 1999;Santschi and Roberts, 2002;Xu et al, 2014). Previous work by the current authors has demonstrated that negligible Pu present in environmental contaminated soils (from the AWE Aldermaston site) is released into solution (<0.01%) under induced-reducing conditions, suggesting that little Pu is mobilized despite the inferred dissolution of oxide minerals and presence of microorganisms linked to Pu reduction (Kimber et al, 2012).…”
Section: Introductionmentioning
confidence: 82%